PENGARUH PARTISIPASI PENYUSUNAN ANGGARAN TERHADAP SENJANGAN ANGGARAN DENGAN KOMITMEN ORGANISASIONAL SEBAGAI VARIABEL MODERATING - Agustami, Silviana; Arfan, Dina (Program Studi Akuntansi FPEB UPI, 2015)
This study aims to analyze: 1) The effect of budgetary participation participation on budgetary slack on SOEs with head office in Bandung 2) Organizational commitment as a variable that moderate the influence between the participation of budget preparation against budget slack.The data used are primary data obtained from 91 respondents are middle managers and lower level managers who participated and responsible in the process of budget preparation on SOEs headquartered in the city of Bandung through non probability sampling. The analysis used is simple linear regression statistic analysis and MRA data analysis. The results of this study indicate that; First, there is a significant influence between the variable of budgeting participation on budget slack which yields R Square 12,1%. Second, the influence of budgetary participation on budgetary slack is not moderated by organizational commitment resulting in R Square 21.3% and significance of -0.009. Thus organizational commitment has a negative effect on the participation of budget formulation on budgetary slack.